Differences In Surface Hardness of Nanohybrid Composite Resin after Immersion In Variant Of Yakult Probiotic Drink - Nurinaya, Fatati; Benyamin, Benni; Feranisa, Anggun; Muchaeroni, Isa Anshori (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: A probiotic drink is an acidic drink. Each type of probiotic drink has different contents. Differences in the surface hardness of composite resin can be caused by the content and pH which damages the bonds of the composite resin which causes a decrease in the hardness of the composite resin. This study aims to determine the difference in surface hardness of nanohybrid composite resin after soaking in the Original and Light Yakult probiotic drinksMethod: The type of the study was laboratory experimental study with post-test design with 2 treatment group. The samples used in this study were FiltexTM Z250 XT nanohybrid composite resin with 32 specimens with a length of 12 mm, width of 2 mm, and thickness of 2 mm. Samples were divided into 2 groups, group A soaked in the Original variant of Yakult and group B soaked in Light variant of Yakult. Samples were soaked for 24 hours in the incubator. Surface hardness of the samples was measued after treatment using Micro Vickers Hardness TesterResult: The results of soaking according to Vickers measurement were tested statistically using the Independent-T Test. The results of the study showed the difference in surface hardness of nanohybrid composite resin after soaking in the Original variant of Yakult and Light variant of Yakult (P<0,05) with an average hardness of 45.81 in Original variant of Yakult and 50.43 in Light variant of YakultConclusion: it can be concluded that soaking in the Original Yakult probiotic drink reduces the surface hardness of composite resin compared to Light Yakult.